Agrinex: A low-cost wireless mesh-based smart irrigation system - Tiglao, Nestor Michael (Animo Repository, 2020)
Wireless Sensor Networks in precision agriculture utilize natural resources more efficiently by collecting real-time data on farms to assist agriculture farmers to make intelligent decisions. Using this technology, farmers can effectively use the information to achieve greater yields and earn higher profits. This work presents an alternative to existing monitoring methods in the agricultural lands whilst providing an irrigation mechanism to help in resource conservation efforts by the use of a Wireless Sensor and Actuator Network (WSAN). Agrinex system features a mesh-like configuration of in-field nodes that act both as the sensor for soil moisture, temperature and humidity and actuator on a valve that regulates drip irrigation. The mesh-based network is dynamically design to allow self-reorganization of sensor nodes when changes happen in the network. The resulting Agrinex system is a promising start for a WSAN framework of various applications particularly in agriculture. © 2020 Elsevier Ltd